SYMBOLIC AND METAPHORICAL COLORISTIC IN THE STRUCTURE OF TANYA PIANKOVA’S NOVEL «THE AGE OF RED ANTS» - Fotuyma, Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Tanya Piankova, a well-known Precarpathian writer, impressed her readers with the new novel "The Age of Red Ants," in which she approached the problem of understanding the great tragedy of the Ukrainian people - the Holodomor of 1932-1933. We understand that the author relied primarily on real facts that are documented, or/and on witnesses’ accounts. For her, the process of preserving and transferring to future generations historical memory, which is a necessary condition for the existence of culture, played an important role. The purpose of the article: to define the role and place of colour semantics in the process of transmitting artistic thought, which passes from the category of visual meaning, acquiring a perceptual form in the text, to analyze the psychosemantic load of colrosemes, to comprehend the role of colorations in the individual picture of the world by T. Piankova. Research methods: concrete-historical, hermeneutical, semantic, as well as receptive aesthetics. Scientific novelty: for the first time in literary science, the aesthetic aspect of death was synthesized through the prism of metaphorical colour semantics on the basis of T. Piankova's novel "The Age of Red Ants." The practical significance of the article is that fragments of the proposed research can be applied in the process of in-depth analysis on the proposed topic.